2008
DOI: 10.1007/bf03256129
|View full text |Cite
|
Sign up to set email alerts
|

The association of adherence to antiretroviral therapy with healthcare utilization and costs for medical care

Abstract: Background-The association between antiretroviral adherence, healthcare utilization and medical costs has not been well studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 38 publications
0
21
0
4
Order By: Relevance
“…In contrast, in a U.S. study by Gardner et al [69], better adherence to cART was associated with higher direct medical costs despite lower rates of hospitalization in more adherent individuals. The differences in the relative contribution of cART costs to overall costs probably accounts for the apparent discrepancy among the studies conducted in South-Africa (where the cART cost component accounted only for 9% of total costs) and in the U.S. (where ART costs represent 60% of total costs).…”
Section: Non-adherence To Antiretroviral Therapy and Its Impact Onmentioning
confidence: 86%
See 1 more Smart Citation
“…In contrast, in a U.S. study by Gardner et al [69], better adherence to cART was associated with higher direct medical costs despite lower rates of hospitalization in more adherent individuals. The differences in the relative contribution of cART costs to overall costs probably accounts for the apparent discrepancy among the studies conducted in South-Africa (where the cART cost component accounted only for 9% of total costs) and in the U.S. (where ART costs represent 60% of total costs).…”
Section: Non-adherence To Antiretroviral Therapy and Its Impact Onmentioning
confidence: 86%
“…The data discussed above showed that in resource-limited settings, where cART comprises a smaller proportion of overall health care costs, excellent adherence to antiretroviral therapy is cost saving [68]. In resource rich settings, better adherence decreases health care utilization, but is not cost saving [69]. However, it is important to note that no formal cost-effectiveness analyses of adherence to antiretroviral therapy have been completed to date.…”
Section: Non-adherence To Antiretroviral Therapy and Its Impact Onmentioning
confidence: 99%
“…The total estimated cost of the service in 2012 was €973 ppm, nearly 90% of which was due to the cost of HAART. While it is difficult to compare costs across countries, HAART is reported to account for 60%-80% of the total cost of HIV care (including inpatient care) in many studies in developed countries [27-33]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition to sexual risk behaviors, it is increasingly recognized that poor adherence to antiretroviral therapy (ART), and to HIV clinical care and treatment more generally, is associated with higher risk of HIV transmission due to failure to suppress HIV viral levels to undetectable levels [12–15]. Poor adherence is also associated with poorer clinical outcomes for PLWHA [16–18] and has high societal costs (e.g., tertiary treatment, lost productivity) [19, 20]. Adherence to care and treatment remains a challenge for many HIV infected patients [9, 21,22] and deserves attention in secondary HIV prevention efforts.…”
Section: Introductionmentioning
confidence: 99%